Exploring the Impact of Leader Efficacy and Emotional Intelligence on Team Performance - Rakhmetullina, Saadat; Pauknerová, Daniela, 1970-; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The present study aims to fill the knowledge gap regarding the influence of emotional intelligence (EI) on leadership efficacy in the setting of Kazakhstan. Even though emotional intelligence (EI) is widely acknowledged as important in leadership studies, little is known about its particular implications for Kazakh leaders. The study, which employs a qualitative methodology with semi-structured interviews, discovers that among Kazakh leaders, EI has a major impact on both team performance and leadership efficacy. Even with the lack of previous studies in this area, exemplary leaders in Kazakhstan actively use emotional intelligence (EI). This study highlights the critical role that EI plays in effective leadership.
Vedoucí práce: Daniela Pauknerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses